Strategi Komunikasi Interpersonal Anak Sulung dalam Menjaga Keterikatan Emosional Pasca Kematian Ayah - Tumadir A kansa; M. Fikri Akbar; Sandy Allifiansyah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The death of a father, as the central family figure, triggers significant changes in family structure and dynamics, necessitating effective communication strategies to maintain emotional bonds among members. This study explores the interpersonal communication strategies used by the eldest child to preserve emotional attachment with the mother and younger siblings after the father's death. Employing a qualitative phenomenological approach, the research examines the eldest child's role as an emotional mediator, practical supporter, and family bond strengthener through in-depth interviews and non-participant observation with bereaved families. Key findings reveal dominant strategies including open communication, structured empathy, active listening, conflict mediation, and clear role and responsibility allocation to minimize ambiguity. These practices foster a sense of security, solidarity, and family adaptation to the new circumstances. Theoretically, this study enriches family communication literature in crisis contexts; practically, it provides recommendations for counselors, social workers, and family members to design communication interventions supporting recovery and cohesion post-loss. The impact of this research lies in its potential to guide family communication frameworks and psychosocial support programs, ensuring that grieving families can transform loss into resilience and sustain long-term relational well-being.